Security and terror: American culture and the long history of colonial modernity - Jelly-Schapiro, Eli (University of California Press, 2018)
"When in 1492 Christopher Columbus set out for Asia but instead happened on the Bahamas, Cuba, and Hispaniola, his error inaugurated a specifically colonial modernity. This is, Security and Terror contends, the colonial modernity within which we still live. And its enduring features are especially vivid in the current American century, a moment marked by a permanent War on Terror and pervasive capitalist dispossession. Resisting the assumption that September 11, 2001, constituted a historical rupture, Eli Jelly-Schapiro traces the political and philosophic genealogies of security and terror--from the settler-colonial conquest of the New World to the wars in Afghanistan, Iraq, and beyond. A history of the present crisis, Security and Terror also examines how that history is registered and reckoned with in significant works of fiction and theory. In critical dialogue with novels by Teju Cole, Mohsin Hamid, Junot Díaz, and Roberto Bolaño, and the theoretical interventions of Jean Baudrillard, Giorgio Agamben, Judith Butler, Michael Hardt and Antonio Negri, and others, Jelly-Schapiro reveals how the erasure of colonial history enables the perpetual reproduction of colonial culture"--Provided by publisher